Hubungan Pengetahuan dan Dukungan Suami dengan Pemilihan Alat Kontrasepsi dalam Rahim (AKDR) pada Wanita Usia Subur (WUS) di Puskesmas Ambarawa Kabupaten Semarang - Mutia Rahmadani (Universitas Ngudi Waluyo, 2024)
Family planning is one way to reduce the rate of population growth and improve the health status of mothers and children. Knowledge about family planning is very important for acceptors to have in choosing the contraceptives to be used. Intrauterine device (IUD) is a contraceptive that does not contain hormone, In Ambarawa health center out of 10 KB acceptors, most mothers have less knowledge about KB and lack of husband support. Husband support is the husband's involvement in providing support to women undergoing their reproductive duties. The purpose of this study was to determine the relationship between knowledge and husband's support with the selection of intrauterine device (IUD) in women of childbearing age (WUS) at Puskesmas Ambarawa Semarang Regency in 2023. This research design is a correlational analytic using a cross sectional approach. The population in this study were all KB acceptor mothers recorded at the Ambarawa Health Center from January to September 2023. The research sample amounted to 87 family planning acceptors. with proportional random sampling technique. Bivariate analysis in this study used the chi-square test. After analyzing using the chi square test, the results showed that there was a relationship between knowledge and the selection of AKDR contraceptives with a p-value of 0.000 <0.05, and there was a relationship between husband's support and the selection of AKDR contraceptives with a p-value of 0.010 <0.05. Abstrak Keluarga Berencana (KB) merupakan salah satu cara untuk menekan laju pertumbuhan penduduk serta meningkatkan derajat kesehatan ibu dan anak. Pengetahuan mengenai KB sangat penting untuk dimiliki oleh akseptor dalam memilih alat kontrasepsi yang akan dipergunakan, di puskesmas Ambarawa dari 10 aseptor KB sebagian besar ibu memiliki pengetahuan kurang mengenai KB dan kurangnya dukungan suami. Dukungan suami merupakan keterlibatan suami dalam bentuk memberi dukungan kepada wanita menjalani tugas reproduksinya. Tujuan dari penelitian ini untuk mengetahui hubungan pengetahuan dan dukungan suami dengan pemilihan alat kontrasepsi dalam rahim (AKDR) pada Wanita usia subur (WUS) di Puskesmas Ambarawa Kabupaten Semarang tahun 2023. Desain penelitian ini merupakan analitik korelasional dengan menggunakan pendekatan cross sectional. Populasi dalam penelitian ini adalah 687 seluruh ibu akseptor KB yang terdata di di Puskesmas Ambarawa dari bulan Januari - September 2023. Sampel penelitian berjumlah 87 akseptor KB. dengan tehnik pengambilan proporsional random sampling. Analisis bivariat dalam penelitian ini menggunakan uji chi-square. Setelah melakukan analisa menggunakan uji chi square didapatkan hasil Ada hubungan antara pengetahuan dengan pemilihan alat kontrasepsi AKDR dangan nilai p-value 0,000<0,05, dan Ada hubungan dukungan suami dengan pemilihan alat kontrasepsi AKDR dangan nilai p-value 0,010<0,05.